2019
DOI: 10.1097/md.0000000000017672
|View full text |Cite
|
Sign up to set email alerts
|

Association between prenatal exposure to bisphenol a and birth outcomes

Abstract: Background: Previous studies investigated the relation of prenatal exposure to bisphenol A (BPA) and birth outcomes, but these results were inconsistent. The aim of this study was to investigate the relation of prenatal exposure to BPA and birth outcomes, provide comprehensive results based on current studies. Methods: The PubMed, Cochrane databases, and Web of Science databases were searched systematically by two researchers respectively from their inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 40 publications
2
25
1
1
Order By: Relevance
“…These results have to be interpreted with caution, since the association of BPA with fetal head circumference was no longer significant after multiple testing correction. Two previous meta-analyses reported no association between fetal exposure to BPA and gestational age at birth [7,8]. Similarly, in our study, maternal pregnancy-averaged and trimester-specific bisphenol concentrations were not associated with the risk of preterm birth or with gestational age at birth.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…These results have to be interpreted with caution, since the association of BPA with fetal head circumference was no longer significant after multiple testing correction. Two previous meta-analyses reported no association between fetal exposure to BPA and gestational age at birth [7,8]. Similarly, in our study, maternal pregnancy-averaged and trimester-specific bisphenol concentrations were not associated with the risk of preterm birth or with gestational age at birth.…”
Section: Discussionsupporting
confidence: 62%
“…Of the three meta-analyses concerning BPA and birth outcomes, two reported no consistent associations of fetal exposure to BPA with weight, length or head circumference at birth, while one reported positive associations with birth weight [6][7][8]. Two studies evaluated maternal BPA urine concentrations during pregnancy with repeated measures of fetal growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Korean Mothers and Children’s Environmental Health (MOCEH) study revealed significant positive associations between maternal BPA exposure and higher birth weight, which were stronger in male neonates [ 97 ]. A recent meta-analysis of seven independent studies showed a similar direction of association between BPA and higher birth weight [ 98 ]. Prenatal BPA exposure has also been linked with sex-specific changes in hypothalamic–pituitary–adrenal axis function, and the epigenome-wide methylation analysis of cord blood DNA similarly identified sex-specific effects [ 99 , 100 ].…”
Section: Resultsmentioning
confidence: 94%